2011
DOI: 10.1016/j.jcrs.2010.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Ocular toxicity after intracameral injection of very high doses of cefuroxime during cataract surgery

Abstract: Intracameral injection of high doses of cefuroxime induced anterior and posterior inflammation. Without surgical intervention, the final visual outcome was satisfactory in all cases. Long-term retinal function, however, must be assessed through repeated ERG recordings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1
16

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 21 publications
(22 reference statements)
3
85
1
16
Order By: Relevance
“…Our study showed this change to be maintained at 2 years. Tehrani et al 2 3) 0.10 G 0.06 0.12 G 0.14 .194 4th-order spherical aberration (Z4,0) 0.21 G 0.14 0.11 G 0.12 .007* in total RMS wavefront error from preoperatively to all values postoperatively (P Z .008), which we did not observe in our study.…”
contrasting
confidence: 66%
“…Our study showed this change to be maintained at 2 years. Tehrani et al 2 3) 0.10 G 0.06 0.12 G 0.14 .194 4th-order spherical aberration (Z4,0) 0.21 G 0.14 0.11 G 0.12 .007* in total RMS wavefront error from preoperatively to all values postoperatively (P Z .008), which we did not observe in our study.…”
contrasting
confidence: 66%
“…Some cited the lack of a commercially available preparation that would eliminate the risk for dilution errors and the resulting ocular toxicity as their reason for not using it. 3 We have found intracameral cefuroxime to be an effective prophylaxis in our setting. South African ophthalmologists should be encouraged to use this prophylaxis.…”
Section: Endophthalmitis Prophylaxis With Intracameral Cefuroxime In mentioning
confidence: 70%
“…A series of 6 cases was published by Delyfer et al documenting the inadvertent administration of high-dose (100 mg/mL) intracameral cefuroxime at the end of an uneventful cataract surgery, secondary to misunderstanding of the dilution protocol. 19 Each case resulted in moderate anterior inflammation and fibrin formation consistent with a mild form of toxic anterior segment syndrome or toxic endophthalmitis, which had resolved by day 5. All patients developed extensive macular edema with an associated serous retinal detachment on day 1 postoperatively, which significantly improved in the first week.…”
Section: Discussionmentioning
confidence: 93%